Propuesta pedagógica: Arquitectura I - VI - Silberfaden, Daniel Horacio; Posik, Guillermo; Reynoso, Pablo Daniel (La Plata : s.n., 2014)
Contenido: Propuesta pedagógica y plan de actividades.
Keywords: PROPUESTA PEDAGOGICA; ENSEÑANZA; EDUCACION UNIVERSITARIA; CONCURSOS; LA PLATA; FAU; 2014; ARQUITECTURA; SILBERFADEN-POSIK-REYNOSO